Morphological and phylogenetic insights resolve Plenodomus sinensis (Leptosphaeriaceae) as a new species - Tennakoon, Danushka S.; Phookamsak, Rungtiwa; Wanasinghe, Dhanushka N.; Yang, Jun-Bo; Lumyong, Saisamorn; Hyde, Kevin D. (Phytotaxa, 2017)
Plenodomus species were collected from Tamarindus indica L. (Fabaceae) and Plukenetia volubilis L. (Euphorbiaceae) in Yunnan Province, China and subjected to morphological and molecular analysis. Morphologically novel collections comprise unique characters in having mucilaginous globoid-shaped apical and basal appendages (1.5–1.8 μm) and wider third cell from the apex in ascospores. Phylogenetic analysis (Maximum-likelihood, maximum-parsimony and Bayesian analyses) of combined LSU, SSU and ITS sequence data reveal that these collections differ from all other species in the genus. Therefore, a novel species, Plenodomus sinensis is introduced in this study. The new species is compared with other Plenodomus species and a comprehensive description and micrographs are provided.